Peran Manajemen Kepemimpinan dalam Meningkatkan Efektivitas Organisasi: Strategi Pengelolaan Tim untuk Mencapai Tujuan Organisasi secara Optimal - Nursafana, Ely Irma (Maliki Interdisciplinary Journal, 2026)
Leadership management has a very important role in improving organizational effectiveness through good team management. Leadership is not only related to position, but also to a person’s ability to influence, direct, and build cooperation among organizational members in order to achieve common goals. This paper aims to determine the role of leadership management in improving organizational effectiveness through team management strategies. The method used is a literature study by collecting various sources from books and journals related to leadership management and organizations. The results of the discussion show that effective leadership management can create good communication, improve teamwork, and support the implementation of management functions such as planning, organizing, implementing, and supervising. In addition, solid teamwork can increase the creativity, productivity, and quality of work of organizational members. Therefore, the implementation of good leadership management can help organizations achieve their goals optimally and face various challenges in the future.